2021
DOI: 10.1111/aji.13413
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin modifies the in vitro LPS‐induced chemotactic capabilities in human fetal membranes at the term of gestation

Abstract: Problem: Immune responses of fetal membranes involve the production of chemoattractant mediators causing infiltration of maternal and fetal leukocytes, intrauterine inflammation and potentially the disruption of maternal-fetal tolerance. Prolactin (PRL) has deep immunoregulatory effects in the fetal-maternal interface. We aimed to test the in vitro PRL effect upon chemotactic capacities of human fetal membranes. Method ofStudy: Fetal membranes and umbilical cord blood were collected from healthy non-laboring c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Finally, and based on the present and previous results obtained by our group, we can support that PRL can modulate the upstream pro-inflammatory and pro-chemotactic response (Flores-Espinosa et al 2017Núñez-Sánchez et al 2021) and the downstream "second wave" led by MMPs.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, and based on the present and previous results obtained by our group, we can support that PRL can modulate the upstream pro-inflammatory and pro-chemotactic response (Flores-Espinosa et al 2017Núñez-Sánchez et al 2021) and the downstream "second wave" led by MMPs.…”
Section: Discussionsupporting
confidence: 85%
“…Relaxin induces chorionic trophoblast and decidual cell production of uterotonic inflammatory cytokines 207 . Similarly, in vitro models have shown that prolactin causes increased chemotaxis at the choriodecidual junction 208 . Elevation of proinflammatory gene expression has also been reported in the choriodecidual region in spontaneous labor; however, increases in anti‐inflammatory IL‐10 production in response to various infectious agents have also been reported at the choriodecidual junction 209,210 .…”
Section: Exosomal Fir Causes Immune Imbalance At the Fetomaternal Int...mentioning
confidence: 99%
“…Different doses of ovine PRL were used to treat chicken bursa of fabricius cells, and all doses of PRL increase the mitotic activity of cells, and the lowest dosage of PRL is most effective (Bhat et al, 1983 ). Moreover, PRL modified the difference in the chemotactic factor and the leukocyte migration of fetal membranes in a tissue-specific manner (Núñez-Sánchez et al, 2021 ). Our previous results showed that pre-incubating DF-1 cells with PRL before ALV-J infection elicits the best antiviral effects regardless of dose in vitro (Mo et al, 2021 ).…”
Section: Prolactin and The Immune Systemmentioning
confidence: 99%